Pengaruh Latihan Passing Bawah Menggunakan Media Dinding dan Berpasangan Terhadap Peningkatanteknik Passing Bawah Bolavoli Pada Ekstrakurikuler SMP Al-Irsyad Cikukulu Kabupaten Sukabumi Tahun 2018/2019 - Kurniawan, Kurniawan (FKIP Universitas Muhammadiyah Sukabumi, 2019)
In this case the researcher used method True Eksperimental Design quantitave model by pre-test post-test design technical. Sample of the research are 16 student extracurricular volleyball Junior High School Al-Irsyad, by taking totally sample technic. The Instrument of the research wich tested by wall media.analysis technic used statistic paramentric taired sample test and independent sample test. The analysis result are Sig ( 2- tailed) < 0, 05. Sig ( 2- tailed) 0,000 < 0,05 its mean Ho rejected and H1 accepted, the meaning are (1) there are significant effect by training which used wall media concerning result basic technic passing down volleyball. (2) there are significant effect which used passing partner train concerning result of basic technic passing down volleyball. (3) there are better significant effect by training which used wall media compared used passing partner training volleyball. Based on analysis result it could be see that first group has increasing passing down 29.38%. Meanwhile second group has increasing passing down 23.63%. The conclusion are the first group has greater increasing percentage passing down technic than second group percentage